Development of a measure for perceived employment relationship quality (PERQ) - Potgieter, Willem; Olckers, Chantal; Ehlers, Lukas (African Journal of Employee Relations, 2019)
Studies have shown that employees react negatively towards negative supervisory behaviour. Therefore, a questionnaire that could measure the quality of various aspects of the employment relationship could be a useful tool for managing and promoting healthy employment relationships. In the light of this, the aim of this study was to develop a questionnaire that measured the perceived quality of the employment relationship from the employee’s perspective. A quantitative cross-sectional survey was conducted on a non-probability convenience sample of 248 employees from various organisations and sectors in South Africa. Although a 39-item questionnaire was developed across four theoretical dimensions, namely trust, fairness, good faith and justice, the analysis revealed that only two dimensions, labelled social factors and compliance factors and measured by 20 items, were sufficient to measure the desired construct. This questionnaire, which measures the perceived employment relationship quality, could be used as a diagnostic tool by management and HR professionals to determine the state of supervisory relationships in an organisation, and to address any problems brought to the fore, thereby avoiding turnover costs related to negative workplace relationships.